2021
DOI: 10.37268/mjphm/vol.21/no.3/art.1201
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Regarding Covid-19 Among Primary School Students in Kedah, Malaysia: A Cross-Sectional Study

Abstract: Since, children are affected by the coronavirus in the same way as adults, examining the children's knowledge, attitude, and practice (KAP) on COVID-19 would help in building a pandemic-resilient society. Therefore, the present study aims to investigate the knowledge, attitude, and practice regarding COVID-19 among primary school students. This online, cross-sectional study was conducted from May 18 to 20, 2021 among students aged 9 to 12 years old and having access to WhatsApp messenger on their smartphones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…19 A study conducted in Malaysia in 1207 shows that 56% of students had good knowledge with 73.75% of correct responses which is way more than the current findings. 20 Another study conducted in New Delhi shows that 39.6% of students had good knowledge and 60.29% of students had average knowledge which is way more that the current study findings. 21 As this shows that the current finding is not consistent with the others studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…19 A study conducted in Malaysia in 1207 shows that 56% of students had good knowledge with 73.75% of correct responses which is way more than the current findings. 20 Another study conducted in New Delhi shows that 39.6% of students had good knowledge and 60.29% of students had average knowledge which is way more that the current study findings. 21 As this shows that the current finding is not consistent with the others studies.…”
Section: Discussionsupporting
confidence: 58%
“…22 Attitude is also an important part of health promotion behavior, in this study the participant shows 35.66% of students had a favorable attitude towards COVID-19 which is way less than the study conducted in southern Ethiopia in 2021 which found that the 70.9% of the 422 of students had a positive attitude toward the COVID-19 and 86.5% in another study. 20,23 Attitude can be changed with an increase in knowledge and health-seeking behavior. The researcher conducted a brief session on the correct technique of hand washing, use of masks, and social distancing behavior to improve the attitude and practice of school students regarding COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For knowledge, scores above ≥ 70 % were considered good, 50% and 70% were considered fair, and less than 50% were considered poor. It is measured by 12 items 4-point Likert scale (Ganaprakasam et al, 2021). The mean scores of students' attitudes are divided into three levels: mean scores between 3.01 -4.00 are considered good, 2.01 -3.00 are considered fair, and 1.00 -2.00 are considered poor.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments are fun for students because they allow them to expand their knowledge and satisfy their natural curiosity while helping them develop a more scientific mindset (Kurniawan et al, 2019). Six studies (Dubik et al, 2021;El Sayed & Mahmoud, 2021;Ganaprakasam et al, 2021;Getawa et al, 2022;Wen et al, 2020;Yesuf & Abdu, 2022) presented the practice of avoiding crowded places during the COVID-19 pandemic, and there is 71% (95% CI: 24, 74) of the participants avoided the crowded places. However, fewer students practice avoiding crowded places than the study participants of Raquib et al (2022).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Table5shows the subgroup analysis of KAPs toward COVID-19 among various study groups. Studies conducted byGanaprakasam et al (2021) andXue et al (2021) focused only on the KAPs of COVID-19 among elementary school students Wen et al (2020). andHuang et al (2021) included elementary and high school students in their KAPs studies.…”
mentioning
confidence: 99%